Hardware MPI message matching: Insights into MPI matching behavior to inform design. (27th February 2019) - Ferreira, Kurt; Grant, Ryan E.; Levenhagen, Michael J.; Levy, Scott; Groves, Taylor
Summary: This paper explores key differences of MPI match lists for several important United States Department of Energy (DOE) applications and proxy applications. This understanding is critical in determining the most promising hardware matching design for any given high‐speed network. The results of MPI match list studies for the major open‐source MPI implementations, MPICH and Open MPI, are presented, and we modify an MPI simulator, LogGOPSim, to provide match list statistics. These results are discussed in the context of several different potential design approaches to MPI matching–capable hardware. The data illustrate the requirements for different hardware designs in terms of performance and memory capacity. This paper's contributions are the collection and analysis of data to help inform hardware designers of common MPI requirements and highlight the difficulties in determining these requirements by only examining a single MPI implementation.